2016
DOI: 10.2495/ut160091
|View full text |Cite
|
Sign up to set email alerts
|

Safety awareness of roadside traders in Osogbo Township, Osun State, Nigeria

Abstract: The study focuses on evaluating the safety awareness of roadside traders along the major axis of Osogbo, Osun state, Nigeria. The objectives include to identify the location where street traders operate, assess their socio-economic characteristics, identify the risks involved and determine the traders' awareness of the risks involved in their activity. A total of 278 roadside traders were selected from six clusters on the basis of streets using stratified random sampling techniques. Findings reveal that road-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…However, even though street vendors' actions have a detrimental influence on the environment and transportation in general, in particular the traders, according to [15] the challenges of being hit by cars, losing property, being exposed to high concentrations of air pollutants like vehicle exhaust, being exposed to the hot sun and inclement weather, being a victim of crime and theft, sexual harassment, and kidnapping are all things that people have to deal with every day. While [15] additionally emphasized that security officers with legal authority to take and confiscate the goods of traders who break the street trading legislation engage in all kinds of conflicts with roadside vendors (see Figure 5).…”
Section: Effects Of the Encroachment By Informal Sectors Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even though street vendors' actions have a detrimental influence on the environment and transportation in general, in particular the traders, according to [15] the challenges of being hit by cars, losing property, being exposed to high concentrations of air pollutants like vehicle exhaust, being exposed to the hot sun and inclement weather, being a victim of crime and theft, sexual harassment, and kidnapping are all things that people have to deal with every day. While [15] additionally emphasized that security officers with legal authority to take and confiscate the goods of traders who break the street trading legislation engage in all kinds of conflicts with roadside vendors (see Figure 5).…”
Section: Effects Of the Encroachment By Informal Sectors Activitiesmentioning
confidence: 99%
“…[19] asserted that most of the hawkers and squatters that encroached on the roadside right of way or urban green space do that out of ignorance about the extant planning and development control laws and legislation and their presence in the space for economic survival attracts others that join them, and this constitutes free traffic flow hindrance and environmental sanitation issues. [6], [15], [17] revealed that the majority of those involved in the hawking, street trading and squatting activities by the roadside, open space or in the traffic are those with low levels of education or that haven't gone to school, so it is a survival venture for them because they lack the qualification that can make them be engaged into formal employment.…”
Section: Survival Strategies For the Unemployed Youthmentioning
confidence: 99%